PENGARUH WILLIAM FLEXION EXERCISE TERHADAP KEMAMPUAN FUNGSIONAL PADA NYERI PUNGGUNG BAWAH MYOGENIK - Zita Lachika Anung; Mei Kusumaningtyas; Yoga Handita Windiastoni (Poltekkes Kemenkes Jambi, 2023)
Background: Sedentary behavior has a risk of causing low back pain and results in decreased functional ability. William flexion exercise (WFE) is an exercise to improve lumbar stability by strengthening the abdominal muscles and stretching the back muscles. The aim of the study was to determine the effect of the addition of william flexion exercise on functional abilities in patients with myogenic low back pain at Banyumas General Hospital. Methods: This type of research was one group pre test & post test with control design, subjects were randomly selected into the treatment group and the control group. The subjects were 31 patients at the Banyumas General Hospital who included the inclusion criteria. Result: The paired t-test and independent t-test which were carried out in both groups after receiving the intervention obtained a value of p = 0.000 (p <0.05) which means that there was an increase in functional ability and there was a significant difference in the two groups. Difference in mean pre-post test treatment group 7.5 and control 2.4. Conclusion: The addition of william flexion exercise has an effect on increasing functional ability in patients with myogenic low back pain.